#TITLE_ALTERNATIVE# - FITRIANDA NIM : 30713011, EKA
Diabetes mellitus is a group of diseases characterized by state of hyperglycemia due to insufficient secretion of insulin, insulin action, or both. The state of chronic hyperglycemia in diabetes mellitus can lead to long-term damage, dysfunction and failure of a number of organs, especially eyes, kidneys, nerves, heart, and blood vessels. Extract of Centella asiatica or gotu kola has been shown to have antidiabetic activity both empirically and experimentally. However, investigation is needed to determine which compounds are actually responsible for the activity. Further, the action mechanism of the compounds in reducing blood glucose levels, and the safety profile of its use as a drug ingredient should also be investigated. This study aimed to find the active antidiabetic fraction and compound in leaves of gotu kola, and to find the mechanism of action of the compound, as well as to obtain safety profile of active fraction. To achieve these objectives, the research series were designed as follows: separation of saponin-rich and non saponin fractions from ethanolic extract of gotu kola leaves; investigating in vitro antidiabetic activity of extract, fractions and asiaticoside compound using alpha glucosidase inhibition method, alpha amylase inhibition method and glycation inhibition method; investigating in vivo antidiabetic activity using oral glucose tolerance test, alloxan induction method and high lipid-carbohydrate diet induction method in animal (in vivo testings were done using dosage of 125, 250 and 500 mg/kg for extract; 75, 150 and 300 mg/kg for fractions; 1.4, 2.8 and 5.6 mg/kg for asiaticocide); as well as oral acute and repeated doses toxicity of active antidiabetic fraction. In vitro activity test showed that the extract, saponin-rich fraction and asiaticoside compound of pegagan leaves were active as antidiabetes. The IC50 of extract, saponin-rich fraction and asiaticoside in inhibiting alpha glucosidase activity were 372,5, 175,5 and 14,6 μg/ml, while IC50 in inhibiting alpha amylase activity were 266,8,173, 8 and 30.2 μg/ml respectively. But no inhibition was detected in antiglycation test of these samples. On oral glucose tolerance test, extract, saponin-rich fraction and asiaticoside significantly suppressed blood glucose levels increase from 15 to 60 minutes after the glucose loading. The respective increased in glucose levels in the 15 th , 30 th and 60 th minutes after glucose loading in the extract group at dose of 500 mg/kg were 68%, 57% and 8%; in saponin-rich fraction at dose of 300 mg/kg were 94%, 92% , and 11%; and in the asiaticoside group at dose of 5.6 mg/kg were 92%, 79% and 7% of baseline levels (before glucose loading) respectively. The increase in glucose levels of control group were 169%, 124% and 65% of baseline. In alloxan-induced diabetic animals, extract, saponin-rich fraction and asiaticoside lowered glucose and HbA1c levels significantly and increased insulin levels, even thought there was no improvement in pancreatic Langerhans island damage due to alloxan. Significant decrease in glucose levels began after 14 days of administration of all test doses. The highest decrease of fasting blood glucose level after 21 days of administration of test preparation was shown by extract group at dose of 500 mg/kg by 21%, saponin-rich fraction at dose of 300 mg/kg by 9% and asiaticoside at dose of 5.6 mg/kg by 23%. Significant decrease in HbA1c levels compared to control group only occurred in group of extract at dose of 500 mg/kg, saponin-rich fraction at dose of 300 mg/kg, and asiaticoside at dose of 5.6 mg/kg which were 2.04, 2.01, and 2.11 ng/ml respectively, compared to HbA1c levels in the control group of 2.76 ng/ml. Significant increase in insulin levels were detected in the extract, saponin-rich fraction and asiaticoside groups at all doses. The highest insulin levels were obtained from the extract group at dose of 500 mg/kg (19.4 μIU/ml), saponin-rich fraction at dose of 300 mg/kg (24.8 μIU/ml), and asiaticoside at dose of 5.6 mg/kg (27.8 μIU/ml), compared to the control group of 7.28 μIU/ml. Meanwhile, no increase in the number of the island Langerhans and changes in the shape and size after treatment with the test materials. In insulin-resistant animal models induced with high fat-carbohydrate diet, decreased levels of glucose and HbA1c, and increased values of insulin tolerance test constant were only seen in extract and saponin-rich fraction groups, while asiaticoside did not exhibit similar activity although it could reduce fatty deposits arround the hepatocytes in test animals. Significant decrease in glucose levels started from 7 th day of dosage administration. The highest decrease of blood glucose level were measured on 21 st day in group of extract at dose of 500 mg/kg by 26%, and saponin-rich fraction at dose of 300 mg/kg by 25%. After 21 days of administration there was also a significant increase in insulin tolerance test constant values in the extract and saponin-rich fraction group. The increase of insulin tolerance test constant in extract group at dose of 500 mg/kg and saponin-rich fraction at dose of 300 mg/kg were 25% and 24% respectively. Significant decrease in HbA1c levels also occurred after 21 days of extract and saponin-rich fraction administration at all doses. Lower HbA1c levels were shown by extract at dose of 250 mg/kg (1.82 ng/ml) and saponin-rich fraction at dose of 150 mg/kg (1.79 ng/ml), compared to HbA1c in control group (2.25 ng/ml). Meanwhile, histologic observation showed that administration of extract, saponin-rich fraction, and asiaticoside reduce fat deposit in hepatocytes of liver tissue. Oral acute toxicity test results of saponin-rich fraction showed that LD50 of the fraction was higher than 5000 mg/kg. The results of oral subchronic toxicity test using repeated dose method for 28 days showed that in general saponin-rich fraction did not cause significant changes in the parameters observed. Despite changes in some hematological parameters in female animals, which showed mean corpuscular hemoglobin concentration (MCHC) values at dose of 500, 1000 mg/kg and control satellites at 22, 20, and 32 g/dl compared to control group values of 29 g/dl, and decreased platelet counts at dose of 500 and 1000 mg/kg to 310,000 and 289,000 compared to control group values of 435,000, but the values of these parameters were within normal limits. The results of in vitro and in vivo studies showed that the ethanolic extract of gotu kola leaves had antidiabetic activity by inhibiting alpha amylase and alpha glucosidase enzymes, increasing insulin levels, as well as increasing sensitivity to insulin. Saponin-rich fraction is an active antidiabetic fraction of the leaves of gotu kola, and asiaticoside compound is one of the compounds responsible for the antidiabetic activity. The dominant mechanism of action of the saponin-rich fraction as antidiabetic is increasing insulin sensitivity, beside increasing insulin levels and inhibiting the activity of alpha amylase and alpha glucosidase enzymes, while the dominant mechanism of action of asiaticoside is inhibiting the activity of alpha amylase enzyme. In addition the latter also inhibits the activity of alpha glucosidase enzyme and increase levels of insulin. The saponin-rich fraction belongs to the category of practically non-toxic substances with LD50 of higher than 5000 mg/kg and does not produce in toxicity symptoms in repeated oral dosing for 28 days.